The power of material control of the popular legislative initiative by the bureau of the chambers in the admission process. Comentary to STC 143/2024, of december 20 (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2025)
In the judgment presented here, the Constitutional Court declares unconstitutional and null the agreement of the Bureau of the Parliament of Catalonia of February 20, 2024, by which it admitted for processing the popular legislative initiative regarding the Bill for the Declaration of the Independence of Catalonia.For the Constitutional Court, the agreement to qualify and admit for processing a popular legislative initiative is more than a procedural act, whose effects are limited to the Chamber. The agreement also demonstrates the institutional will of the Autonomous Community, which makes it susceptible to challenge before the Constitutional Court.Furthermore, the judgment considers that the qualification and admission for processing of a popular legislative initiative by the Bureau of the Legislative Assembly not only constitutes formal and substantive control of its purpose in accordance with the Constitution, sectoral legislation, and constitutional doctrine, but also delimits the exercise of the right to political participation enshrined in article 23 of the Spanish Constitution.
Keywords: Popular legislative initiative; qualification and admission process